Containment, Holding, and Receptivity: Somatopsychic Challenges - Baum, Scott (Bioenergetic Analysis, 2017)
This paper is about some principles in the organization of the psychotherapeutic space. These are central, basic principles, which are necessary for the space to work as intended. These principles include: the primacy of the welfare of the patient; the therapist’s ability to prioritize the experience of the patient; the necessity that the therapist be versatile in the dynamics of holding and engagement; and that the therapist have a grasp of her or his personality dynamics, how they may intrude into the therapeutic space, when that can be harmful and what to do if the intrusion is destructive. A perspective derived from principles of Bioenergetic Analysis is shown to be useful in elaborating the dynamics of the space. This paper is also about the challenges posed by the requirement to establish an environment based on these principles. This construction demands a great deal from therapists. At the end of the paper I will propose that facing these challenges and the work to meet them offers a model for psychotherapy and also for relationships more broadly.